2022
DOI: 10.3390/biomedicines10092091
|View full text |Cite
|
Sign up to set email alerts
|

Role of CA 19.9 in the Management of Resectable Pancreatic Cancer: State of the Art and Future Perspectives

Abstract: Background: Surgery still represents the gold standard of treatment for resectable pancreatic ductal adenocarcinoma (PDAC). Neoadjuvant treatments (NAT), currently proposed for borderline and locally advanced PDACs, are gaining momentum even in resectable tumors due to the recent interesting concept of “biological resectability”. In this scenario, CA 19.9 is having increasing importance in preoperative staging and in the choice of therapeutic strategies. We aimed to assess the state of the art and to highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Recurrence patterns are also related to the prognosis, as patients with metastatic disease localized to the lung have been shown to have a signi cantly longer survival than those with metastatic disease localized to the liver [15]. Serum CA19-9 is a crucial tumor marker for PDAC, and several reports have validated its clinical utility in the diagnosis and monitoring of disease progression [23], as well as in predicting early recurrence after surgery for PDAC. Previous studies identi ed preoperative CA19-9 as an important predictor for early recurrence either within 6 or 12 months for patient cohorts who underwent upfront surgery as well as those who received neoadjuvant chemoradiotherapy [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence patterns are also related to the prognosis, as patients with metastatic disease localized to the lung have been shown to have a signi cantly longer survival than those with metastatic disease localized to the liver [15]. Serum CA19-9 is a crucial tumor marker for PDAC, and several reports have validated its clinical utility in the diagnosis and monitoring of disease progression [23], as well as in predicting early recurrence after surgery for PDAC. Previous studies identi ed preoperative CA19-9 as an important predictor for early recurrence either within 6 or 12 months for patient cohorts who underwent upfront surgery as well as those who received neoadjuvant chemoradiotherapy [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the preoperative levels of CA 19-9 are negatively associated with the overall survival, nodal involvement, and margin status positivity in resectable PC. However, some limitations impair the role of CA 19-9 in PDAC preoperative staging and management[ 74 ], including up to 50% of PDAC patients without CA 19-9 secretion.…”
Section: Diagnostic and Prognostic Markers For Pancreatic Cancermentioning
confidence: 99%
“…Recently, a prospective multicenter phase 2 trial demonstrated promising results when gemcitabine plus nab-paclitaxel chemotherapy were administered before surgery[ 18 ]. Even though the data supporting the use of neoadjuvant therapies in resectable PDACs are more limited, this strategy is proposed in patients with “biological” borderline resectable tumors ( e.g., radiological resectable PDACs with elevated levels of Ca-199)[ 19 ].…”
Section: Introductionmentioning
confidence: 99%